2015
DOI: 10.1136/heartasia-2015-010644
|View full text |Cite
|
Sign up to set email alerts
|

Lean body mass index prognostic value for cardiovascular events in patients with coronary artery disease

Abstract: ObjectiveLittle is known about the relationship between body composition indicators, including body mass index (BMI), fat mass index (FMI) and lean BMI (LBMI), and adverse outcomes after percutaneous coronary intervention (PCI) in Asian populations. The aim of this study was to clarify this relationship.MethodsThe SHINANO registry is a prospective, observational, multicenter cohort registry that enrolled 1923 consecutive patients with coronary heart disease (CHD) from August 2012 to July 2013; 66 patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 30 publications
4
26
0
Order By: Relevance
“…Likewise, sarcopenia, defined as a loss of muscle mass and associated with frailty and overall decreased functionality and increased mortality, could have harmful effects in patients with CAD, as our results suggest 23, 24, 25…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Likewise, sarcopenia, defined as a loss of muscle mass and associated with frailty and overall decreased functionality and increased mortality, could have harmful effects in patients with CAD, as our results suggest 23, 24, 25…”
Section: Discussionmentioning
confidence: 60%
“…[20][21][22] Likewise, sarcopenia, defined as a loss of muscle mass and associated with frailty and overall decreased functionality and increased mortality, could have harmful effects in patients with CAD, as our results suggest. [23][24][25] Overall, the inability of BMI to discriminate between fatfree mass, a protective factor, and fat mass, a factor associated with adverse outcomes, may lead to erroneous assumptions about risk of MACEs in patients with CAD and may explain why, in our cohort, BMI was not associated with MACEs. 5,6,26,27 Thus, the results of our study could not confirm the obesity paradox that has been reported in several other studies in those with CAD, [28][29][30][31][32] heart failure, [33][34][35][36] and atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the adjusted mean values of echocardiographic parameters reflecting diastolic dysfunction, remodeling and hypertrophy were significantly associated with increased BMI. These findings indicate the proportional relationship between functional and structural LV abnormalities and the degree of 29 In particular, several studies show a U-shaped association between cardiovascular death and BMI, which implies an adverse influence of underweight on cardiovascular disease. 26-28 This discrepancy appears to be attributable to features of our study design and participants.…”
Section: Discussionmentioning
confidence: 98%
“…25(OH)D, the half-life of which is close to 3 weeks and the concentration of which in blood is stable, is the most valuable indicator for evaluating the individual nutritional status of vitamin D. The current widely accepted vitamin D nutritional status evaluation criteria are shown in Table 1-1 (37) . (37) The prevalence of vitamin D deficiency in China is high (38) (39) . In 5531 (5-101 years old) urban Beijing residents reporting for health check-up, vitamin D deficiency and severe vitamin D deficiency percentages were 87.1 and 44.7, respectively (38) .…”
Section: Figure 1-2 Reported Incidence Of Vitamin D Deficiency Aroundmentioning
confidence: 99%
“…In 5531 (5-101 years old) urban Beijing residents reporting for health check-up, vitamin D deficiency and severe vitamin D deficiency percentages were 87.1 and 44.7, respectively (38) . A cross-sectional study including 6014 healthy elderly adults (≥ 60 years) showed that 34.1% of men and 44.0% of women presented with vitamin D deficiency (39) . A study of 418 Chinese immigrant population with mean age of 56 years in the Netherlands found that the prevalence of vitamin D deficiency in men and women was 67.9% and 53.1%, respectively (40) .…”
Section: Figure 1-2 Reported Incidence Of Vitamin D Deficiency Aroundmentioning
confidence: 99%